Analysis Macroeconomic On Islamicity Performance Index Through Fund Third Parties The Islamic Cooperation - Oyong Lisa (Universitas Pendidikan Ganesha, 2017)
This study aimed to analyze the effect of macroeconomic consisting of the exchange rate, inflation and Bi rate to deposit and islamicity performance index, analyze the influence of third party funds to islamicity performance index. analyze the influence of the macroeconomic performance index islamicity through third-party funds. The samples used in the study of 76 cooperatives of sharia in Indonesia. The analysis technique used path analysis. Based on the results of the analysis indicated that the macroeconomic path which consists of the exchange rate and the BI rate significantly influence third-party funds and islamicity performance index, while inflation does not affect the third-party funds and islamicity performance index. Third party funds islamicity significant effect on the performance index. Third party funds were able to mediate the effect of the exchange rate and the BI rate to islamicity performance index through third party funds.Keywords: Islamicity Performance Index, third party fund, Exchange Rate, inflation, BI rate.